2011
DOI: 10.1002/cmdc.201100285
|View full text |Cite
|
Sign up to set email alerts
|

Azabicyclo[3.1.0]hexane‐1‐carbohydrazides as Potent and Selective GHSR1a Ligands Presenting a Specific in vivo Behavior

Abstract: Buon appetito! The synthesis and in vitro and in vivo profiles of a novel series of potent and selective ghrelin ligands is presented. Selected compounds share the same “atypical” ghrelin antagonist profile already observed with the recently disclosed compound GSK1614343, thus exhibiting the same ability to promote food intake and body weight gain in rodents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…To date, the majority of nonpeptide compounds have claimed to be antagonists, with the exception of Pasternak et al () who identified an inverse agonist with poor p.o. bioavailability (Rudolph et al , ; Perdonà et al , ; Sabbatini et al , ; Mihalic et al , ; Puleo et al , ; Moulin et al , ). PF‐05190457 is an equipotent inverse agonist and neutral competitive antagonist working independently of ghrelin tone with the added advantage of not switching to a partial agonist.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of nonpeptide compounds have claimed to be antagonists, with the exception of Pasternak et al () who identified an inverse agonist with poor p.o. bioavailability (Rudolph et al , ; Perdonà et al , ; Sabbatini et al , ; Mihalic et al , ; Puleo et al , ; Moulin et al , ). PF‐05190457 is an equipotent inverse agonist and neutral competitive antagonist working independently of ghrelin tone with the added advantage of not switching to a partial agonist.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Numerous methods have been developed for the construction of azabicyclo[3.1.0]hexanes. [10] These include the Kulinkovich/de Meijere reaction [11,12] , cyclisation of tethered amines with metals (Pd [13] , Ru [14] , Rh [15] , Ag [16] ), cyclisation of tethered cyclopropanes [17] , and the Simmons-Smith [18] /CoreyChaykovsky [19] /sulfur ylide-Au [20] cyclopropanations. These methods are usually only effective in the synthesis of one specific type of scaffold.…”
Section: Dedication ((Optional))mentioning
confidence: 99%
“…To allow for late-stage variation of the aryl substituent on the pyrazole a tetrahydropyranyl (THP)-protected pyrazole was employed. The pyrazolo-pyrimidinone core was assembled with THP at R2 (20). Then THP-deprotection gave 21 followed by Chan-Lam coupling to give the desired arylated compounds 22 (along with their N-1 regioisomers).…”
Section: Resultsmentioning
confidence: 99%
“…12 We are interested in identifying GHS-R1a antagonists and inverse agonists for the treatment of obesity. Several structurally diverse antagonists have been reported 9,10,[13][14][15][16][17][18][19][20][21][22] and some have been shown to act as inverse agonists. 19,22 We were attracted to a quinazolinone series reported to have demonstrated CNS exposure (Fig.…”
Section: Introductionmentioning
confidence: 99%